Motivation and gender as determinants of achievement in senior secondary school economics (2011)
"The paper considered the relationship between motivation and students' achievement, as well as male and female students' cognitive achievement in Secondary School Economics in lbadan North Local Government Council Area of Oyo State. The population for the study was made up of all Economics students in the Local Government Area. Two-stage sampling was employed to randomly select four schools from forty Senior Secondary Schools in the area and an intact arm of SSll from each of the sampled schools. Two instruments constructed and validated by the researchers were administered on the subjects; the resulting data were then collated and analysed using correlation and t-test. Results showed that motivation is positively related with students' cognitive achievement; likewise, gender also has no significant effect on students' cognitive achievement in Economics. The result also showed that there was no significant difference in the cognitive achievement in Economic on gender basis. Recommendations included: that all learners irrespective of gender and family background be given equal level playing ground in their study; that every student irrespective of sex or background be given the same level of encouragement and the necessary equipment be made available in the same quantum to all student for equal access and opportunities to the study of Economics. "